Brain networks associated with cognitive and hedonic responses to a meal. Issue 6 (23rd January 2017) - Pribic, T.; Kilpatrick, L.; Ciccantelli, B.; Malagelada, C.; Accarino, A.; Rovira, A.; Pareto, D.; Mayer, E.; Azpiroz, F.
Abstract: Background: We recently reported interrelated digestive, cognitive, and hedonic responses to a meal. The aim of this study was to identify brain networks related to the hedonic response to eating. Methods: Thirty‐eight healthy subjects (20‐38 age range) were evaluated after a 5‐hour fast and after ingestion of a test meal (juice and warm ham and cheese sandwich, 300 mL, 425 kcal). Perceptual and affective responses (satiety, abdominal fullness, digestive well‐being, and positive mood), and resting scans of the brain using functional MRI (3T Trio, Siemens, Germany) were evaluated immediately before and after the test meal. A high‐order group independent component analysis was performed to investigate ingestion‐related changes in the intrinsic connectivity of brain networks, with a focus on thalamic and insular networks. Key Results: Ingestion induced satiation (3.3±0.4 score increase; P <.001) and abdominal fullness (2.4±0.3 score increase; P <.001). These sensations included an affective dimension involving digestive well‐being (2.8±0.3 score increase; P <.001) and positive mood (1.8±0.2 score increase; P <.001). In general, thalamo‐cortical connectivity increased with meal ingestion while insular‐cortical connectivity mainly decreased. Furthermore, larger meal‐induced changes (increase/decrease) in specific thalamic connections were associated with smaller changes in satiety/fullness. In contrast, a larger meal‐induced decrease in insular‐anterior cingulate cortex connectivity was associated with increased satiety, fullness, and digestive well‐being. Conclusions and Inferences: Perceptual and emotional responses to food intake are related to brain connectivity in defined functional networks. Brain imaging may provide objective biomarkers of subjective effects of meal ingestion. Abstract : Meal ingestion induces cognitive and hedonic sensations, and our aim was to identify brain networks related to these sensations. Perceptual and emotional responses to food intake are related to brain connectivity in defined functional networks. Brain imaging may provide objective biomarkers of subjective effects of meal ingestion.